The Manusela Limestone in Seram: Late Triassic Age for A ‘Jurassic’ Petroleum Play - Tim R. Charlton; J.T. (Han) van Gorsel (Berita Sedimentologi, 2014)
A well-known Mesozoic hydrocarbon exploration target in eastern Indonesia is the ‘Jurassic Limestone Play’, validated by the Oseil oilfield in NE Seram. However, there is no biostratigraphic evidence to support a Jurassic age for the Manusela Limestone that forms the reservoir in this play, while numerous paleontological studies on outcrops and wells instead document only Late Triassic faunas and microfloras.We here review the paleontological literature on Seram and suggest that the Manusela Limestone is of latest Triassic (Late Norian-Rhaetian) age, while the Early-Middle Jurassic interval is condensed or absent over the structural highs established as a result of the Manusela Limestone accumulation. This revised (but in reality 100 years old) age model fits well in Tethys-wide trends where sponge- and algae-dominated reefs blossomed during the Norian-Rhaetian from the Alps to NW Australia-Papua New Guinea, while a major extinction event at the end of the Triassic caused a collapse of carbonate reef systems globally, leading to a virtual absence of reefal limestones during the Early-Middle Jurassic.